The Role of Nonconventional Technologies in the Extraction Enhancement and Technofunctionality of Alternative Proteins from Sustainable Sources - da Silva Carvalho, Cleberyanne [UNESP]; Ojoli, Gabriela Xavier [UNESP]; Paco, Mariana Grecco [UNESP]; Bonetti, Nathalia Almeida [UNESP]; de Pinho, Samantha Cristina; do Prado Silva, Jéssica Thais [UNESP]; Polachini, Tiago Carregari [UNESP] (MDPI, 2025)
In recent decades, the consumption of animal proteins has been rethought by consumers. Factors such as improved health and sustainability are key aspects of this scenario. Studies have sought innovative and sustainable technologies to improve protein extraction from alternative sources to increase their competitiveness. In this sense, the aim of this work was to combine the effects of nonconventional extraction methods on the process yield and the resulting techno-functional properties extracted from alternative proteins. The literature contains significant publications regarding the use of ultrasound (US), pulsed electric fields (PEFs), microwaves (MWs) and deep eutectic solvents (DESs) for enhancing protein extraction. Re-emerged techniques such as reverse micelles and aqueous two-phase extraction have also been reported. For this reason, the present study aimed not only to present the obtained results but also to discuss how the mechanisms associated with the aforementioned technologies impact the extraction yield and modification of proteins. In general, US tends to increase protein solubility (20-30%) and emulsifying capacity (35%); MWs can increase protein yield (25%) while reducing extraction time (50-70%); DES-based extraction tends to retain more than ~40% of the native functionality, and PEFs have demonstrated up to a 20% improvement in protein recovery. Nonconventional extraction methods have varying effects on the characteristics and quality of extracted proteins, offering benefits and challenges that should be considered when choosing the most suitable technology. The specificity related to each technology can be used to make possible interesting industrial applications involving nonanimal proteins.